2007
DOI: 10.1007/s00441-007-0436-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cells expressing Jun and Fos proteins and synthesizing DNA in the adrenal cortex of hypophysectomized rats: regulation by ACTH and FGF2

Abstract: Protein expression of the early response genes, jun and fos, has been suggested to play an important role in the in vitro and in vivo proliferation of adrenal cells. To elucidate the immunolocalization of proliferative cells and the patterns of adrenal gland expression of members of the activating protein-1 (AP-1) family of oncogenes, we used hypophysectomized rats. The effects of adrenocorticotropic hormone (ACTH) and fibroblast growth factor 2 (FGF2) on Fos and Jun protein expression were investigated, and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
5
0
2
Order By: Relevance
“…Previous findings from our laboratory have shown that ACTH administration in hypophysectomized (Hyp) or Dextreated rats induces S-phase entry in all zones of the adrenal cortex, which confirms that the adrenocortical proliferative capacity is not restricted to the outer adrenal zone (Baccaro et al 2007;Torres and Lotfi 2007). Moreover, these studies have implicated the AP-1 family of transcription factors in the regulation of the cell cycle during ACTH-induced proliferation in the adrenal cortex .…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Previous findings from our laboratory have shown that ACTH administration in hypophysectomized (Hyp) or Dextreated rats induces S-phase entry in all zones of the adrenal cortex, which confirms that the adrenocortical proliferative capacity is not restricted to the outer adrenal zone (Baccaro et al 2007;Torres and Lotfi 2007). Moreover, these studies have implicated the AP-1 family of transcription factors in the regulation of the cell cycle during ACTH-induced proliferation in the adrenal cortex .…”
Section: Introductionsupporting
confidence: 71%
“…Conversely, evidence is also available that each zone can be renewed from within itself. Although proliferation is more frequent in the subcapsular/glomerulosa cell zone, it is not restricted to this region, since cell proliferation also occurs in the ZF and ZR (McEwan et al 1999;Baccaro et al 2007;Torres and Lotfi 2007). Additionally, there is evidence that POMC-derived peptides other than ACTH play a role in the control of adrenal growth.…”
Section: Discussionmentioning
confidence: 89%
“…Products encoded by these genes regulate transition of mouse Y1 and H295R cells from G 0 /G 1 to S phase of the cell cycle (43,49). Similar mechanisms control proliferative activity of rat adrenocortical cells in vivo (50). Our study revealed that ACTH, CER and desCER have a potent stimulatory effect on expression of the Fos gene in cultured rat adrenocortical cells, however, expression of Jun gene was unaffected.…”
Section: Discussionmentioning
confidence: 51%
“…Jun and Fos protooncogenes were identified as important transcription factors activated very early (10 minutes) after partial hepatectomy [19]. In adrenocortical cells Fos gene is induced by both ACTH and Fgf2 [5860]. In our experiments in the beginning of regeneration (days 1-2) only Fos gene has been found to be upregulated, while between days 5 and 15 after enucleation a lowered expression of both genes has been found.…”
Section: Discussionmentioning
confidence: 59%